2011
DOI: 10.1016/j.febslet.2011.10.037
|View full text |Cite
|
Sign up to set email alerts
|

BLT2 phosphorylation at Thr355by Akt is necessary for BLT2-mediated chemotaxis

Abstract: Edited by Masayuki MiyasakaKeywords: Leukotriene B 4 receptor 2 (BLT2) Chemotaxis Akt Reactive oxygen species a b s t r a c t BLT2, a low-affinity leukotriene B 4 (LTB 4 ) receptor, is a member of the G protein-coupled receptor family and is involved in multiple cellular responses, including chemotaxis. Despite its biological significance, the mechanisms of BLT2 regulation, especially by protein kinases, are poorly characterised. In this study, we found that Akt phosphorylates BLT2 at its C-terminal Thr 355 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…RanBPM overexpression attenuated, whereas knock‐down promoted, BLT 2 receptor‐mediated motility and generation of ROS in response to either LTB 4 or 12HHT (Wei et al ., ), suggesting that RanBPM may act as a negative regulator of BLT 2 receptor signalling in cell motility. Finally, the BLT 2 receptor dissociation from RanBPM was dependent on phosphorylation of BLT 2 receptors at Thr 355 , a site previously identified by the same investigators as critical for LTB 4 ‐induced BLT 2 receptor‐mediated chemotaxis through PI3K‐Akt signalling (Wei et al ., ).…”
Section: Blt Receptorsmentioning
confidence: 97%
“…RanBPM overexpression attenuated, whereas knock‐down promoted, BLT 2 receptor‐mediated motility and generation of ROS in response to either LTB 4 or 12HHT (Wei et al ., ), suggesting that RanBPM may act as a negative regulator of BLT 2 receptor signalling in cell motility. Finally, the BLT 2 receptor dissociation from RanBPM was dependent on phosphorylation of BLT 2 receptors at Thr 355 , a site previously identified by the same investigators as critical for LTB 4 ‐induced BLT 2 receptor‐mediated chemotaxis through PI3K‐Akt signalling (Wei et al ., ).…”
Section: Blt Receptorsmentioning
confidence: 97%
“…However, little attention has been focused on the function of BLT2 on proliferation, migration and barrier integrity of bronchial epithelial cells. In the current study, we explored the contribution of BLT2 in functions of 16HBE cells by manipulating the expression of BLT2 in 16HBE cells, and then treating with BLT2 antagonist (LY255283 (Li, Haribabu, Mathis, Kim, & Gozal, 2011)) or BLT2 specific agonist (12-HHT [Okuno et al, 2008] or CAY10583 [Wei, Kim, & Kim, 2011]).…”
mentioning
confidence: 99%
“…We have previously reported that BLT2-mediated ROS generation and chemotactic motility are regulated by AKT phosphorylation. 16 , 17 , 26 Therefore, we next assessed whether BLT2 D196G leads to enhanced AKT phosphorylation. As shown in Figure 5a , AKT phosphorylation was significantly enhanced (approximately twofold increase) in cells expressing BLT2 D196G and treated with low-dose LTB 4 or 12-HHT stimulation ( Figure 5b ) compared with BLT2-transfected cells.…”
Section: Resultsmentioning
confidence: 99%
“… 15 Additionally, the overexpression of BLT2 causes an LTB 4 -induced increase in chemotactic responses in a ROS-dependent manner. 16 , 17 In addition, activation of Akt by LTB 4 , which phosphorylates BLT2 at Thr 355 , is critical for BLT2-mediated chemotactic responses. 17 Furthermore, recent studies have indicated that the LTB 4 -BLT2 axis is critical for the pathogenesis of inflammatory diseases, including asthma, 13 , 18 carotid atherosclerosis, 19 , 20 and cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation